1991
DOI: 10.1136/bjo.75.9.524
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations in fetal alcohol syndrome.

Abstract: Eight children with the fetal alcohol syndrome are described with ocular anomalies. They all had a strong history of maternal alcohol abuse throughout pregnancy, especially in the first trimester. All the children had eye abnormalities. These included external eye lesions, Peters' anomaly, lens opacification, ocular motility disorders, and optic nerve hypoplasia.Fetal alcohol syndrome is characterised by at least three of the following findings: (1) A 6-month-old boy was born at 41 weeks gestation with meconi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 10 publications
3
51
1
2
Order By: Relevance
“…This finding is reassuring, given the high prevalence of ocular abnormalities reported previously in children diagnosed with FAS. 2,4,5,6,8,9,[13][14][15][16]18,19,[23][24][25] Although many studies have reported a high rate of major eye malformations in children with FAS, little is known about children who are exposed to high levels of alcohol but do not develop FAS, despite the fact that most heavily alcohol-exposed children do not develop FAS. Only 2 previous studies of the visual system in alcohol-exposed children included children who did not have FAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is reassuring, given the high prevalence of ocular abnormalities reported previously in children diagnosed with FAS. 2,4,5,6,8,9,[13][14][15][16]18,19,[23][24][25] Although many studies have reported a high rate of major eye malformations in children with FAS, little is known about children who are exposed to high levels of alcohol but do not develop FAS, despite the fact that most heavily alcohol-exposed children do not develop FAS. Only 2 previous studies of the visual system in alcohol-exposed children included children who did not have FAS.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These disorders may include external eye malformations, intraocular abnormalities, and impaired visual acuity. 3,4,19 Previous investigations had limitations, including studying only children with FAS who were referred for ophthalmologic evaluation because of known or suspected problems, providing little or no information on the extent of in utero alcohol exposure, performing limited evaluations of visual function, and examining only a small number of subjects. As a result, little is known regarding the risk of eye malformations in children who were exposed to high levels of alcohol in utero but did not develop FAS.…”
Section: Conclusion Previous Research Has Found That Children With Fmentioning
confidence: 99%
“…185 ONH frequently occurs in children with the foetal alcohol syndrome. [186][187][188] Anecdotally, there seems to be considerable variation in the association of alcohol ingestion and ONH, with studies from the USA and Scandinavia showing a close association, but those from other countries, where alcohol intake is just as high, nationally, showing a lower correlation. 134 ONH in maternal diabetes: Diabetic mothers have babies with a higher incidence of neurological anomalies, including optic disc hypoplasia.…”
mentioning
confidence: 99%
“…Así mismo, debe evidenciarse: 1) un patrón característico de anormalidades faciales menores que incluya dos o más de las características faciales típicas del síndrome; 2) uno o más defectos estructurales congénitos mayores entre los siguientes: a) cardiacos: comunicación interauricular, transposición de los grandes vasos, defectos septales ventriculares, defectos cardiacos conotruncales; b) esqueléticos: sinostosis radiocubital, defectos de segmentación vertebral, contracturas articulares, escoliosis; c) renales: aplasia, hipoplasia o displasia renal, riñones en herradura/duplicaciones uretrales; d) oculares: estrabismo, ptosis palpebral, anomalías vasculares de la retina, hipoplasia del nervio óptico; e) auditivos: pérdida de audición conductiva, pér-dida de audición neurosensorial o perceptiva; o dos o más malformaciones menores como: hipoplasia de las uñas, dedos meñiques cortos, clinodactilia de los meñiques, camptodactilia, pliegues palmares anormales (en "palo de hockey"), pectus carinatum/ excavatum, errores refractivos, anomalías del pabellón auricular (25). Esta serie de malformaciones ha sido reportada en numerosos estudios desde los primeros trabajos sistemáticos sobre el tema (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Criterios Diagnósticos Del Saf Y Otros Teafunclassified